Asociación entre obesidad y retinopatía diabética en pacientes adultos con diabetes mellitus tipo 2 - Zamora Mostacero, Víctor Edwin (2018)
To establish whether there is an association between obesity and diabetic retinopathy in adult patients with type 2 diabetes mellitus. METHODOLOGY: An analytical, retrospective and transversal study, in which 102 patient records were reviewed that met inclusion and exclusion criteria. RESULTS: We studied 102 patients (34 cases and 68 controls), in the group of cases, 10 patients with diabetic retinopathy were obese (29%) and 32 patients without diabetic retinopathy were obese (47 %) (Table 1). There were no significant differences between cases and controls regarding the age, the sex and the time of diagnosis. The OR of obese diabetic retinopathy was 0.37 (95% confidence interval [CI], 0.15-0.89, p = 0.0266). The chi-square statistic was 5.0683, with p being 0.024 for a p level of significance <0.05. CONCLUSION: From the present study, we concluded that, the probability of developing diabetic retinopathy in obese patients with DM2 and BMI ≥ 30 kg/m2 is 0.37 times the probability of normal BMI patients with DM2